Synergistic Activity of Nitroimidazole-Oxazolidinone Conjugates against Anaerobic Bacteria - Zhijun Zhuang (Molecules, 2020)
The introductions of the bicyclic 4-nitroimidazole and the oxazolidinone classes of antimicrobial agents represented the most significant advancements in the infectious disease area during the past two decades. Pretomanid, a bicyclic 4-nitroimidazole, and linezolid, an oxazolidinone, are also part of a combination regimen approved recently by the US Food and Drug Administration for the treatment of pulmonary, extensively drug resistant (XDR), treatment-intolerant or nonresponsive multidrug-resistant (MDR) Mycobacterium tuberculosis (TB). To identify new antimicrobial agents with reduced propensity for the development of resistance, a series of dual-acting nitroimidazole-oxazolidinone conjugates were designed, synthesized and evaluated for their antimicrobial activity. Compounds in this conjugate series have shown synergistic activity against a panel of anaerobic bacteria, including those responsible for serious bacterial infections.